2018
DOI: 10.3233/jad-170875
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Amyloid-β42 Production by Fipronil and Other Pyrazole Insecticides

Abstract: Generation of amyloid-␤ peptides (A␤s) by proteolytic cleavage of the amyloid-␤ protein precursor (A␤PP), especially increased production of A␤ 42 /A␤ 43 over A␤ 40 , and their aggregation as oligomers and plaques, represent a characteristic feature of Alzheimer's disease (AD). In familial AD (FAD), altered A␤ production originates from specific mutations of A␤PP or presenilins 1/2 (PS1/PS2), the catalytic subunits of ␥-secretase. In sporadic AD, the origin of altered production of A␤s remains unknown. We hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…the γ‐site) as has been observed for the APP [21,23]. This alteration is detectable as an endophenotype of p3‐Alcα with C‐terminal variants in patients with AD [22] and in cells treated with compounds that modulate γ‐secretase activity [24,25]. These lines of evidence suggest that the function and metabolism of Alcs are also closely involved in AD pathobiology.…”
Section: Introductionmentioning
confidence: 74%
“…the γ‐site) as has been observed for the APP [21,23]. This alteration is detectable as an endophenotype of p3‐Alcα with C‐terminal variants in patients with AD [22] and in cells treated with compounds that modulate γ‐secretase activity [24,25]. These lines of evidence suggest that the function and metabolism of Alcs are also closely involved in AD pathobiology.…”
Section: Introductionmentioning
confidence: 74%
“…However, our results showed that these doses, on the long term, are deleterious in a transgenic mouse model of Alzheimer's disease. Cypro, mepa, and pyri could be considered Alzheimerogen pollutants (Cam et al 2018;Portelius et al 2016) at the subnanomolar regulatory levels (0:1 lg=L) because they accelerated fibrils formation and promoted the progression of disease's markers in the J20 mouse model. We hypothesize that prevention strategies toward pesticide long-term exposure may be an alternative to counterbalance the lack of treatment and to slow down the worldwide Alzheimer's epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…DDT also increases Aβ levels in H4 glioma cells with a APP Swe transgene via elevation of APP and BACE1, while decreasing the levels of Aβ-clearing ATP-binding cassette transporter A1 (ABCA1) and inhibiting the activity of Aβ-degrading insulin-degrading enzyme (IDE) [63]. Aβ production has also been shown to be elevated by triazine herbicides [64] and pyrazole insecticides in various cell lines [65].…”
Section: Pesticides and The Induction Of Alzheimer's Disease Markers mentioning
confidence: 99%
“…A range of pesticides may act in a manner that is termed by Cam and colleagues as environmental "Alzheimerogens' [65], namely by elevating the levels of Aβ [59,[61][62][63][64][65][66]. The authors screened a large compound library using a cell-based assay for enhanced production of the longer Aβ peptides (Aβ42/Aβ43), and identified 9 pyrazole insecticides.…”
Section: Enhancement Of Aβ and Tau Expression Modification And Clearmentioning
confidence: 99%